Hepatoprotective Effect of Bee Bread in Metabolic Dysfunction-Associated Fatty Liver Disease (MAFLD) Rats: Impact on Oxidative Stress and Inflammation - Zaida Zakaria; Zaidatul Akmal Othman; Joseph Bagi Suleiman; Nur Asyilla Che Jalil; Wan Syaheedah Wan Ghazali; Victor Udo Nna; Mahaneem Mohamed (MDPI AG, 2021)
Metabolic dysfunction-associated fatty liver disease (MAFLD) is a pathological accumulation of hepatic lipid closely linked with many metabolic disorders, oxidative stress and inflammation. We aimed to evaluate the hepatoprotective effect of bee bread on oxidative stress and inflammatory parameters in MAFLD rats. Twenty-eight male Sprague-Dawley rats were assigned into four groups (n = 7/group): normal control (NC), high-fat diet (HFD), bee bread (HFD + Bb, HFD + 0.5 g/kg/day bee bread) and orlistat (HFD + Or, HFD + 10 mg/kg/day orlistat) groups. After 12 weeks, the HFD group demonstrated significantly higher body weight gain, serum levels of lipids (TG, TC, LDL), liver enzymes (AST, ALT, ALP) and adiponectin, liver lipids (TG, TC) and insulin resistance (HOMA-IR). Furthermore, the HFD group showed significantly decreased antioxidant enzyme activities (GPx, GST, GR, SOD, CAT) and GSH level, and increased liver oxidative stress (TBARS, NO), translocation of Nrf2 to the nucleus, Keap1 expression and inflammation (TNF-α, NF-κβ, MCP-1) together with histopathological alterations (steatosis, hepatocyte hypertrophy, inflammatory cell infiltration, collagen deposition), which indicated the presence of non-alcoholic steatohepatitis (NASH) and fibrosis. Bee bread significantly attenuated all these changes exerted by HFD feeding. In conclusion, our results suggest that bee bread might have antioxidant, anti-inflammatory, anti-steatotic and anti-fibrotic effects that are beneficial in protecting liver progression towards NASH and fibrosis.